Estimation theory in hydrology and water systems - Nachazel, Karel (Developments in water science, 1993)
Methodological procedures of the theory of estimation of statistical parameters of time series and their application to hydrology and water engineering, particularly the sphere of reservoir-controlled runoffs, are dealt with in this volume. For estimates use is made of random sequences generated for various probability properties. This methodological approach enables examination of the properties of random and systematic errors of the parameters estimated even for the asymmetrical probability distributions, which are frequent in hydrology and water engineering. This book will be of interest to stochastic hydrologists.